KOMUNIKASI KELUARGA DALAM PERSPEKTIF AL-QUR'AN - Sarkawi, Sarkawi; Abdullah, Abdullah; Sikumbang, Ahmad Tamrin (Fakultas Komunikasi dan Desain Program Studi Komunikasi dan Penyiaran Islam, 2025)
Research with the title Family communication in the perspective of the Qur'an, which aims to find out how the Koran regulates and guides families in communication. Especially in the midst of the development of digital media that can affect the joints of life today, so it is interesting to conduct research on family communication in the perspective of the Qur'an, because the family is the beginning of life and communication to plunge into the social environment. The research method used is a descriptive-qualitative approach, in which researchers will collect and analyze literature related to communication in the Qur'an. Based on the discussion carried out, at least it can be understood that family communication must prioritize honesty, openness, gentleness and mutual respect and carry out nonverbal communication by promoting an attitude of compassion, forgiveness, patience and prioritizing deliberation.